Penerapan Model Discovery Learning dapat Meningkatkan Aktivitas dan Hasil Belajar IPA Pada Materi Ciri-Ciri Khusus Makhluk Hidup Siswa Kelas VI MIN 8 Aceh Barat Daya Pelajaran 2018/2019 - Elvianti, Maria (Universitas Serambi Mekkah, 2020)
The purpose of this study is to improve the activities and learning outcomes of science in the material special features of living things through the application of the Discovery Learning model of class VI MIN 8 students in Southwest Aceh 2018/2019 Academic Year. The learning model used in this study is the Discovery Learning model. The subjects of this classroom action research were students in class VI MIN 8 Aceh Barat Daya. The number of students is 27 students with 15 male students and 12 female students. This research was conducted in the 2018/2019 school year within a period of 3 months, from August to October 2018 in odd semester. The methodology of this research is classroom action research consisting of two cycles and each cycle consists of two meetings. Each cycle consists of planning, implementing, observing and reflecting. The research procedure consisted of pre-research, planning cycle one, implementing cycle one, observing cycle one, reflection cycle one, planning cycle two, implementing cycle action two, observing cycle two and reflection cycle two. Data collection techniques are collecting test scores that are carried out at the end of each learning cycle in each cycle using the written test instrument. Learning outcomes data were analyzed by means of percentage descriptive statistics. The results showed that (1) Student learning activities increased from the good enough category and the good category increased to very good (2) The completeness of student learning outcomes from 33.33% pre cycle increased to 59.25% in the first cycle and in the second cycle increased to 85.18 %. The application of the Discovery Learning model has been able to improve the activities and learning outcomes of natural science students on the material of the special characteristics of living creatures of class VI MIN 8 students in Southwest Aceh 2018/2019 Academic Year.